Estimation and Comparison of the Levels of Elastase in Saliva, GCF & Serum of Smokers and Non-smokers with Chronic Periodontitis -A Clinico-biochemical Study - S. Srinivasan (Journal of Global Pharma Technology, 2020)
Objective: This study was done to estimate and compare the levels of Elastase in Saliva, GCF & Serum of smokers and non-smokers with chronic periodontitis. Materials and Method:125 male subjects in the age group of 21-50 years were enrolled and categorized as Group 1, Non-smoking subjects with healthy periodontium Group 2, Smoking subjects with healthy periodontium Group 3, Non-smoking subjects with Chronic periodontitis Group 4, Smoking subjects (10 Cigarettes/day) with Chronic periodontitis. Plaque Index, Gingival Bleeding Index, Probing Pocket Depth, Clinical Attachment Level, Salivary, GCF and Serum Elastase levels were recorded and evaluated using sandwich ELISA method. Results: The clinical parameters expressed a significant difference between diseased group and healthy group. Elastase levels (Saliva, GCF and Serum) showed significant difference between diseased group and healthy group. In between the diseased group comparison, GCF and Saliva showed Lower Elastase levels in smoking periodontitis group. Whereas, Serum showed higher Elastase levels. Conclusion: Elastase can be used as a reliable biomarker for smokers and non-smokers with chronic periodontitis to denote disease activity. Keywords: Periodontitis; Smoking; Elastase; Saliva; Gingival crevicular fluid.